Endoscopic Third Ventriculostomy: Our Experience of Consecutive 50 Cases at a Tertiary Care Center - Ramesh Chandra Venkata Vemula; BCM Prasad; Kunal Kumar (Indian Journal of Neurosurgery)
Objective The aim of this study was to do a retrospective analysis of the various neurosurgical pathologies where endoscopic third ventriculostomy (ETV) was used and to evaluate the outcome and prognosis. Methods The retrospective data collection was done for the patients who underwent ETV with or without other adjunct procedures; the results were prepared for clinical presentation, diagnosis, surgical approach, and surgical goal; and success rate and prognosis were analyzed and compared with other studies. Results A total of 50 patients were included in the study, with overall success rate of ETV as 88%; aqueductal stenosis was the most common indication where ETV was used; headache and vomiting were the most common presenting complaints followed by ataxia and visual blurring; and ETV provided flexibility in its use with biopsy, abscess drainage, temporary external ventricular drain placement, etc. Conclusion ETV being superior to ventriculo-peritoneal shunt for obstructive hydrocephalus provides flexibility in its use and possibly is a useful adjunct to prevent postoperative hydrocephalus after endoscopic intraventricular surgery; proper case selection in accordance to ETV success score yields a better success rate. In experienced hands with proper precautions, perioperative complications can be kept at minimum. Wherever possible, in cases of obstructive hydrocephalus, especially in patients >1 year of age, ETV should be the treatment of choice. We recommend a proper case selection, including preoperative detailed reading of sagittal magnetic resonance imaging scan, to improve the success rate with less complication.